AIRSIDE FACILITIES DESIGN KULON PROGO YOGYAKARTA AIRPORT - Pertiwi, Hanna
Development of Kulon Progo Airport is a solution to overcapacity of Adisucipto International Airport. Three types of aircraft, A330-300, B777-300ER, and B747-400 were use as aircraft design. In addition the flight plan of the biggest aircraft A380 also considered. Air-side facilities design process begin with reviewing Master Plan of Kulon Progo Airport, collecting environment data such as annual rainfall intensity, soil type, and aircraft data. Planning started from geometry, drainage, and pavement thickness. Geometrical analysis done by comparing the result from SKEP 77/VI/2005 regulation with the masterplan planning condition. Number of aircraft traffic analized to findout air-side capacity within hour. The result shows that on the peak hour there are 22 aircraft circulated on the air-side. Drainage planning with different type of channel in order to dispose rainfall immediately. Pavement analysis done by comparing the difference in the thickness of the flexible and rigid pavements. FAARFIELD software is used to calculate the pavement thickness which able to withstand the aircraft load plan. The results of the simulation software generate flexible pavement surface layer thickness of 4 inches, 11,3 inches base, subbase 29,8 inches, while the rigid pavement surface layer obtained 19,1 inches, 4 inches of base and 4 inch subbase. The next analysis is cost analysis, comparing the cost of flexible and rigid pavement based on the estimated unit price prevailing in 2014 lead to the conclusion that flexible pavement is cheaper than rigid pavement. This result can be used as a consideration in the design process of airside facilities Kulon Progo Airport, Yogyakarta. The results of this initial planning based on secondary data and assumptions to be deepened further with detailed planning by using more accurate data.